Synthesis of barbiturate-CU (II) complexes using reflux method and evaluation of their antibacterial activity - Shreekant Ravindra Naik; Dr. Gayatri Barabde; Dr. Sushama Ambadekar (International Journal of Pharma and Bio Sciences, 2020)
Actions of metal ions in biology have gain a huge importance of metal-based therapeutics. The present research work deals with the synthesis of copper (II) complexes synthesized from 5-Arylidene Barbituric acid derivatives; chemical analysis was carried out to identify derivatives (ligand) - metal ratio of these complexes in solution. For the determination of complex nature of the material of these complexes, Mole ratio method has been used. The stability constant of the formed complexes was calculated by molar conductance measurement using Modified Job’s method, which is also known as method of Continuous Variations. Further, synthesized complexes were characterized by UV-visible spectroscopy, Fourier-transform infrared spectroscopy (FTIR), X-ray diffraction, mass spectroscopy as well as NMR physicochemical techniques. Antibacterial effectiveness of the ligand and its metal complexes has been investigated invitro on the growth of Gram-positive Staphylococcus aureus, Bacillus anthracis, Escherichia coli and Klebsiella Pneumonia bacterial strains. The attained electronic spectral bands are characteristic and reliable with the plausible composition of the ligands as well as its metal complexes. It also provides a further example of the coordination of 5-Arylidene Barbituric acid ligands. Absorption peak values of FTIR are characteristic of the ligand as well as coordinated by two oxygen atoms of two ligands molecules and exhibit their metal coordination. NMR 1H,13C signal variations also correlate with the coordination mediated chemical shifts. Both the metal complexes showed significant antibacterial activity. However, enhanced antimicrobial activity of the metal complexes than Ligands against Gram positive was observed.